Relationship Of Exclusive Breastfeeding Of Frequency Of Illnes Events In Baby Age 6-12 Months In Community Health Centers Banyumas - Wuri Utami; Hastin Ika Indriyastuti; Yuliawati Yuliawati (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This research method is using quantitative research methods with observational analytic research with a retrospective cohort approach. The number of samples is 162 respondents. The measuring instrument used was a questionnaire. The results showed the majority of infants who were given exclusive breastfeeding experienced a frequency of rare illness events as many as 59 (72.8%) respondents and infants who were not given exclusive breastfeeding the majority experienced frequent frequency of illness events as many as 50 (61.7%) respondents. The analysis of the study showed that there was a relationship between exclusive breastfeeding and the frequency of illness in infants aged 6-12 months. In this study it was found that the majority of the incidence of illness in infants who were given exclusive breastfeeding was fever as much as 22 (27.2%) while infants who were not exclusively breastfeeding were diarrhea as much as 37 (45.7%).